Improving Village Information Systems through Aerial Mappingfor Simpang Ayam Village, Bengkalis District, Bengkalis Regency: Peningkatan Sistem Informasi Desa melalui Pemetaan Udara untuk Desa Simpang Ayam Kecamatan Bengkalis Kabupaten Bengkalis - Suryanita, Reni; Maizir, Harnedi; Saily, Randhi; Firzal, Yohannes; Roza, Yenita; Olivia, Yessi (Universitas Lancang Kuning, 2025)
Simpang Ayam Village, located in Bengkalis Regency, Riau, possesses significant economic potential, especially in rubber and palm oil plantations. However, limited geospatial data has hindered effective development planning. In this community service project, the University of Riau team employed aerial photography with drones to create a geospatial map of the village. The data collected was processed using Agisoft Photoscan software, resulting in a detailed map of the village's central area, stored in the village's Geographic Information System (GIS). This map provides essential information for targeted infrastructure planning and economic development. Consequently, village officials have access to more accurate data, supporting precise and participatory decision-making. This project is expected to enhance public service quality and promote sustainable village development.